A hidden truth [large type] - Miller, Judith, 1944- (Miller, Judith, 1944- Home to Amana, 2013)
When Karlina Richter finds out that a new shepherd will be sent to East Amana, she fears she'll no longer be able to help her father with the sheep. Her fears increase when Anton Becker arrives and shows little interest in the flock- or in divulging why he's been sent. Dovie Cates decides to visit the Amana Colonies, where her mother spent her formative years. But when Dovie begins to ask questions about her mother's past, no one seems willing to tell her anything.